PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KOLOID KELAS XI IPA SMA NEGERI 12 PEKANBARU - Yayuk Andriyani; Herdini '; Jimmi Copriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purposes of research were to know the improvement of student learning result and categories of learning result by implementing learning model Creative Problem Solving (CPS) on the subject colloid subject at the class XI IPA SMAN 12 Pekanbaru. This research is experimental research using Design Randomized Control Group Pretest-Posttest. The population in the research consist of 3 class, that is XI IPA 1, XI IPA 2, and XI IPA 3. The sample that used consisted of two class, that is class X IPA 2 as experiment class and class XI IPA 1 as control class that has tested by normality and homogeneity test. Experiment class is the class that implemented CPS learning model while the untraeted control class. Data analysis techniques used is the t-test. Results of the analysis it was found that tscore > ttable (3,84 > 1,67), it means that the implementation of learning model CPS can improve students result on the subject of colloid in class XI IPA SMAN 12 Pekanbaru. Categories of learning result of student amount 0,84 with the high categories.Keywords : Learning Model Creative Problem Solving (CPS), Learning Result, Colloid